RISK FACTORS FOR INTRAUTERINE INFECTION IN EXTREMELY PRETERM AND VERY PRETERM BIRTH, COMPLICATED BY THE RUPTURE OF AMNIOTIC MEMBRANES - Шадеева, Юлия Александровна; Гурьева, Валентина Андреевна (Mother and Baby in Kuzbass, 2019)
The purpose of the study was to identify risk factors for intrauterine infection (IUI) of the fetus during prolongation of extremely preterm (22+0-27+6 weeks) and very preterm (28+0-33+6 weeks) births (PB), complicated by the rupture of amniotic membranes. Methods. The course of pregnancy, delivery and the newborns’ neonatal period were studied in 160 patients with prolonged pregnancy complicated by premature rupture of amniotic membranes (PRAM) in extremely preterm and very preterm birth. The analysis of nominal data was performed by calculating the odds ratio; the high-risk thresholds for quantitative variables were calculated using ROC analysis. Results. A statistically significant effect of 21 factors to the risk of IUI of the fetus was found in women with prolonged premature pregnancy complicated by PRAM. The greatest risk resulted from the fetal growth restriction (OR = 17.4; 95% CI: 1.77-171.3), a combination of more than 3 ultrasound markers of infection affecting the placenta, amniotic fluid and fetus (OR = 7.19; 95% CI: 1.85-28.05), gestational pyelonephritis (OR = 7.01; 95% CI: 2.48-19.81), exacerbation of chronic ENT infection (OR = 6.13; 95% CI: 2.14-17.5), long-term threat of miscarriage (OR = 5.6; 95% CI: 2.4-12.7), asymptomatic bacteriuria (OR = 5.3; 95% CI: 2.24-12.5). The lesser risk was caused by STD occurred during pregnancy (chlamydia, mycoplasma, ureaplasma) (OR = 4.34; 95% CI: 1.96-9.6), chronic inflammatory diseases of the pelvic organs (OR = 3.71; 95% CI: 7-8.02), a history of miscarriages (OR = 3.7; 95% CI: 1.73-8.13), chronic pyelonephritis (OR = 3.6; 95% CI : 1.5-8.52), severe oligohydramnios (AFI ˂ 50 mm) (OR = 3.33; 95% CI: 1.52-7.28), early sexual debut (OR = 2.6; 95% CI: 1.07-6.51), chronic inflammatory ENT diseases (OR = 2.6; 95% CI: 1.1-6.3), history of 2 or more abortions (OR = 2.2; 95% CI: 1.04-4.7), nonspecific vaginitis occurred during pregnancy (OR = 2.5; 95% CI: 1.2-5.4), acute respiratory viral infections (OR = 2.5; 95% CI: 1.17-5.41), isthmic cervical insufficiency (OR = 2.3; 95% CI: 1.1-4.9). In addition, the factors increasing the risk of fetal IUI were the gestation period less than 27.5 weeks at the time of PRAM (sensitivity 89.2 %, specificity 77.2 %, AUC 0.84), increased concentration of highly sensitive C-reactive protein more than 6.33 mg/l in maternal blood (sensitivity 80.0 %, specificity 66.7 %, AUC 0.75), increased interleukin level over 11.76 pg/ml (sensitivity 70.0 %, specificity 78.3 %, AUC 0.69). Conclusion. Identifying the risk factors for IUI of the fetus in extremely preterm and very preterm birth induced by the rupture of amniotic membranes enables to apply personalized approach to determine the appropriateness of pregnancy prolongation to reduce adverse perinatal outcomes associated with infection.